Reconstituição de uma poligonal topográfica pelo sistema de posicionamento global: planimetria - Corseuil, Cláudia Weber [UNESP]; Robaina, Adroaldo Dias (Universidade Federal de Santa Maria, 2003)
The objective of this study is to verify the time influence of the GPS receivers for data acquisition in the reconstitution of a topographic polygonal. The determination of the polygonal is determined by the relative static positioning method using two of one frequency GPS receivers at different occupation periods of points (30,15, 10 and 5 minutes), with a two second recording rate. Results of the determination using GPS receivers are compared with the distances, azimuths, horizontal projections, horizontal angles, and the obtained areas of a polygon, on which the topographic elements of this polygon are determined by the perimetrical path using a Total Station. The angles of the polygon obtained by Total Station were calculated by the average of 24 readings and the distances by the average of 12 readings. The results show that the reconstitution of a topographic polygonal depends on the quality of the data collected with the GPS receivers, which are influenced by the time of the occupation points. The 15 minute' occupation time seems to be more appropriated, presenting a small difference (a few centimeters) with respect to the polygonal elements that were analyzed.

Este estudo tem por objetivo verificar a influência do tempo de coleta de dados com receptores GPS na reconstituição de uma poligonal topográfica. O levantamento da poligonal é realizado através do método de posicionamento relativo estático. São utilizados dois receptores GPS de uma freqüência, em diferentes tempos de ocupação dos pontos (30, 15, 10 e 5 minutos) com uma taxa de gravação de 2 s. Os resultados do levantamento com receptores GPS são comparados com as distâncias, azimutes, projeções horizontais, ângulos horizontais e as áreas obtidas de um polígono, cujos elementos topográficos foram determinados por caminhamento perimétrico utilizando uma Estação Total. Os ângulos do polígono levantado por Estação Total, foram calculados através da média de 24 leituras e as distâncias através da média de 12 leituras. Os resultados mostram que a reconstituição de uma poligonal topográfica depende da qualidade dos dados coletados pelos receptores GPS, sendo influenciada pelo tempo de ocupação dos pontos. O tempo de ocupação de 15 minutos demonstra ser o mais adequado para a obtenção de uma diferença centimétrica nos elementos da poligonal que são analisados.
Reconstitution of a topographic poligonal by the global positioning system: Planimetry
Keywords: topographic survey; system GPS; relative static method; levantamento topográfico; sistema GPS; método relativo estático